Advanced Nursing Perspectives on the Assessment, Early Recognition, and Clinical Management of Pediatric Abusive Head Trauma-An Updated Review (The Review of Diabetic Studies, 2024)
Background: Abusive head trauma (AHT) is the leading cause of traumatic brain injury and fatal physical abuse in infants, characterized by complex mechanisms, diagnostic challenges, and severe long‑term consequences.Aim: To provide an updated review of the assessment, early recognition, and clinical management of pediatric AHT from an advanced nursing perspective.Methods: This review synthesizes current evidence on etiology, epidemiology, pathophysiology, clinical presentation, evaluation strategies, and multidisciplinary management, including the critical nursing role.Results: AHT commonly results from shaking, impact, or combined forces, producing subdural hematomas, retinal hemorrhages, diffuse axonal injury, and cerebral edema. Early recognition requires careful history‑taking, comprehensive physical assessment, neuroimaging, laboratory testing, and ophthalmologic evaluation. Effective management depends on ATLS‑based stabilization, intracranial pressure control, seizure prophylaxis, surgical intervention when indicated, and coordinated multidisciplinary care. Nurses play pivotal roles in assessment, monitoring, documentation, and caregiver education.Conclusion: Early identification, standardized evaluation, and evidence‑based management significantly improve outcomes and enhance child safety.